ANALISIS KEPUASAN PELANGGAN SURAT KABAR HARIAN PAGI RADAR BOGOR - Gusmia Arianti; Alim Setiawan Slamet; Mokhamad Syaefudin Andrianto (KOLEGIAL, 2017)
Radar Bogor is a local daily morning newspaper published in Bogor belongs to Jawa Pos Groups. Newspaper competition is more tightly because of new newspapers emergingand consumer preferences changing. The company must plan innovativemarketing strategy based on consumer satisfaction. The purposes of this study were to identify factors influencing customer satisfaction and to analyze the level of customer satisfactionof Radar Bogor newspaper. The method was used IPA-CSI (Important Performance Analysis-Customer Satisfaction Index). The Analysis coverage 29 attributes. High priority attributes to improve were layout design, print quality and quality of review Bogor Raya column. The result of Level Customer Satisfaction Index is 69.24 percent.